PENGARUH EFEKTIVITAS PEMBUKAAN REKENING ONLINE DAN PROMOSI TERHADAP MINAT MENJADI NASABAH BANK SYARIAH INDONESIA (STUDI MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM UIN SULTHAN THAHA SAIFUDDIN JAMBI) - Nurzilawati; Rafidah; Istiqomah, Khusnul (Universitas Sains dan Teknologi Komputer, 2024)
ABSTRACT The rapid development of technology is often used by companies, including Islamic banks, to increase their markets by using existing technology. To improve service to its customers, the bank launched a transaction service media based on information technology, namely mobile banking. Mobile banking services make it easier for customers to carry out banking transactions via mobile devices or Personal Data Assistants.At the end of 2019 Bank Syariah Indonesia launched an online account opening feature in the BSM application service. To introduce this online account opening feature in order to attract customers' interest, promotional activities are important in communicating and influencing customers. In addition, the effectiveness of opening an online account in the form of convenience is also important, because it is immediately felt and used by customers.Therefore the researcher raised the title of the influence of the effectiveness of opening online accounts and promotions on interest in becoming a customer of Bank Syariah Indonesia. This study used a quantitative method, the sample in this study were 97 students, with data collection techniques using the Purposive Sampling technique, in which the selection of samples used certain criteria according to the phenomena and needs studied.Data collection was carried out by distributing questionnaires to students who met the criteria for opening an online account. The results of this study indicate that the effectiveness variable for opening an online account (X1) has a significant and positive effect on interest in becoming a customer (Y), as evidenced by the results of the T test of 0.000 <0.05 with a tcount of 6.435 > 1.662. and the promotion variable (X2) also obtained significant positive results on the interest in becoming a customer of Bank Syariah Indonesia with a T test result value of 0.052 <0.05 with a tcount value of 1.970 > 1.662.